3D image‐guided treatment planning for Ruthenium‐106 brachytherapy of choroidal melanomas. Issue 5 (19th December 2020) - Espensen, Charlotte A.; Kiilgaard, Jens F.; Klemp, Kristian; Gothelf, Anita; Appelt, Ane L.; Fog, Lotte S.
Abstract: Background: Current standard treatment procedures for Ruthenium‐106 (Ru‐106) brachytherapy for choroidal melanomas do not use 3D image‐guided treatment planning. We evaluated the potential impact of introducing 3D treatment planning and quantified the theoretical clinical benefits in terms of tumour control probability (TCP) and normal tissue complication probability (NTCP). Materials and methods: Treatment plans for thirty‐two patients were optimized using 3D image‐guided treatment planning and compared to the original 2D clinical plans. Optimization of plans was done in an image‐based treatment planning system by optimizing the plaque position and treatment time such that the entire tumour received the prescribed dose of 100 Gy. TCP and NTCP for 2D clinical plans and optimized 3D image‐guided plans were estimated from published outcome prediction models and compared within patients using Wilcoxon signed‐rank test. Results: The median minimum tumour dose (D99% ) for 2D clinical plans was 93 Gy (range: 23–158 Gy), corresponding to 5‐year TCP of 75% (IQR 61–86%), while median tumour D99% for optimized 3D image‐guided plans was 115 Gy (range 103–141 Gy), corresponding to TCP of 82% (IQR 80–84%). This was a statistically significant increase in estimated TCP (median increase in TCP 8% (IQR: −5–23, p = 0.006). While the dose to normal tissue increased somewhat, there was no significant change in NTCP. Conclusion: 3D treatment planning theoretically allows for improved tumour dose delivery for Ru‐106 brachytherapy of choroidal melanomas, resulting in a significant increase in expected tumour control compared to traditional approaches using 2D calculations. The deliverability of optimized plans, and potential increased risk of late complications, will have to be confirmed in future clinical studies.